Peran Country Image dalam Membentuk Perceived Product Quality dan Dampaknya pada Purchase Intention Produk Pakan Kucing - Intan Irawati (Journal of Innovative and Creativity, 2025)
This study examines the role of China’s country image in shaping perceived product quality and its impact on purchase intention for Kitchen Flavor, a Chinese-made cat food widely consumed in Jakarta. Using a quantitative approach, data were collected from 100 cat owners aged 17 years or older who had purchased Kitchen Flavor within the past three months. Measurement scales were adapted from Roth and Romeo’s (1992) country image dimensions and Konuk’s perceived quality indicators. Structural analysis using SEM-PLS reveals that innovativeness, prestige, and workmanship/quality significantly enhance perceived product quality, while design/diversity shows no significant effect. Perceived product quality robustly predicts purchase intention, indicating that consumers prioritize product safety, nutritional reliability, and manufacturing standards over visual attributes. Findings also show that positive user experiences and community reviews reduce negative stereotypes toward Chinese products. Overall, perceived quality acts as the key mechanism linking country image to consumer purchasing behavior.